Technical feasibility of the acclimatization system in aviary of posture: A case study - Pereira, Danilo F. [UNESP]; Kodaira, Vanessa [UNESP]; Bueno, Leda G. De F. [UNESP]; Soares, Nilce M. [UNESP]; Salgado, Douglas D'alessandro [UNESP] (FapUNIFESP (SciELO), 2017)
The objective of this study was to compare the performance of laying hens between automated aviaries, one with and another without acclimatized system. On a daily basis it was registered in each aviary the mortality, the egg production, and the feed consumption. The variables of the dry bulb temperature, relative humidity and black globe temperature were registered every 30 minutes using the thermos hygrometer. Every 28 days ninety eggs from each aviary were collected randomly and the variables egg weight, shell weight, shell thickness and Haugh Unit were registered. The consumption and quality of the electrical energy supply were monitored every 30 minutes using registers of electrical magnitude. The results showed that the acclimatization system consumes more electrical energy; however it provides thermal environment more suitable for bird raising, resulting in better production and quality of the eggs. The quality of the electrical energy supply was not maintained, since several interruptions occurred which resulted in higher mortality in the acclimatized aviary. It was concluded that the acclimatization system is technically feasible, since the electrical energy supply is guaranteed.
Keywords: Ambience; Egg production; Electrical energy; Mortality; Precision animal science